Planning Regulations and Budgetary Politics on Equal Access to Islamic Education at the Regional Level - Sopidi; Alwiyah, Lulu; Famuji, Untung; Halim Tamuri, Datuk Ab (Universitas Islam Negeri Raden Intan Lampung, 2026)
Equitable access to Islamic education across various regions of Indonesia continues to face substantial disparities. These inequalities are reflected in significant differences in budget allocation, the availability of educational facilities and infrastructure, and the degree of policy support at the local level between madrasahs and public schools. This study aims to analyze the influence of educational planning regulations and the dynamics of budgetary politics on efforts to achieve equitable access to Islamic education at the regional level. This research adopts a qualitative approach with a policy study design. Data were collected through document analysis of national and regional education regulations, education budget documents (Regional Revenue and Expenditure Budget/APBD and Special Allocation Fund/DAK), as well as official data and publications from the Ministry of Religious Affairs and the Central Bureau of Statistics. Data were analyzed comprehensively using content analysis and public policy analysis techniques. The findings reveal that although educational planning regulations have normatively incorporated the principle of equity in access, the implementation of budgetary politics at the regional level still demonstrates systematic priority biases that tend to disadvantage Islamic education. The study also identifies a lack of synchronization in roles and authorities between local governments and relevant ministries in implementing affirmative policies. Furthermore, education budgeting schemes have not been fully based on the actual needs of Islamic education institutions, as they remain dominated by technocratic formula-based approaches and political considerations. Based on these findings, this study recommends strengthening binding affirmative regulations on budget allocation, improving policy synchronization and coordination between central and local governments, and shifting toward education planning and budgeting models oriented toward equitable access and performance accountability.